Toxic Effect Of Monocrotophos On Various Blood Parameters In Edible Freshwater Fish Oreochromis mossambicus (Tilapia): Life Sciences-Monocrotophos Toxicity - A.Solaiappan; Prakash Sahaya Leon (International Journal of Life Science and Pharma Research, 2022)
In modern agriculture, farmers are using the authenticity of pesticides for agricultural activities. Water bodies are often polluted with various harmfull chemical substances. Fishes are very important for human nourishment. In this study, the effect of Pesticide monocrotophos on various hematological parameters such as RBC, WBC, and Hemoglobin was observed in freshwater fish Oreochromis mossambicus. The fish were exposed to various sub-lethal concentrations (1/10, 1/20, and 1/30) of Monocrotophos for 10, 20, and 30 days. The blood samples were analyzed at the end of every exposure period. Increased count of WBC observed in Lower Sub lethal concentration (21.25, 21.76, 22.01), Medium Sub-lethal concentration (21.69, 22.48, 22.89), and Higher Sub lethal concentration (22.47, 23.54, 23.69) of monocrotophos at various monocrotophos exposure periods on experimental fish Oreochromis mossambicus. Decreased count of RBC observed in Lower Sub-lethal concentration (3.58,3.21,3.08), Medium Sub-lethal concentration (2.97,2.35,2.19) and Higher Sub-lethal concentration (2.41,2.16,2.02) and decreased level of Hemoglobin were observed in Lower Sub-lethal concentration (21.25,21.76,22.01), Medium Sub-lethal concentration (21.69,22.48,22.89) and Higher Sub-lethal concentration (22.47,23.54,23.69) of monocrotophos at various exposure period on fish Oreochromis mossambicus. The 1/10 sub-lethal concentration of monocrotophos showed a high level of variation on 30th-day exposure. Reduction of RBC indicates hemolysis in fish and increased WBC count has been considered to be an adaptation of animals to meet stressful conditions. In the present study, it was found that the effect of monocrotophos alters the activity of various blood parameters in freshwater fish Oreochromis mossambicus. Therefore, the experiment is an attempt to study the toxicity of the pesticide Monocrotophos concerning blood parameters of freshwater fish Oreochromis mossambicus. It is concluded from this study that exposure to Monocrotophos affects the hematological parameters of fish.